Understanding Reactive Oxygen Species in Bone Regeneration: A Glance at Potential Therapeutics and Bioengineering Applications - Sheppard, Aaron J.; Barfield, Ann Marie; Barton, Shane; Dong, Yufeng (Frontiers in Bioengineering and Biotechnology, 2022)
Although the complex mechanism by which skeletal tissue heals has been well described, the role of reactive oxygen species (ROS) in skeletal tissue regeneration is less understood. It has been widely recognized that a high level of ROS is cytotoxic and inhibits normal cellular processes. However, with more recent discoveries, it is evident that ROS also play an important, positive role in skeletal tissue repair, specifically fracture healing. Thus, dampening ROS levels can potentially inhibit normal healing. On the same note, pathologically high levels of ROS cause a sharp decline in osteogenesis and promote nonunion in fracture repair. This delicate balance complicates the efforts of therapeutic and engineering approaches that aim to modulate ROS for improved tissue healing. The physiologic role of ROS is dependent on a multitude of factors, and it is important for future efforts to consider these complexities. This review first discusses how ROS influences vital signaling pathways involved in the fracture healing response, including how they affect angiogenesis and osteogenic differentiation. The latter half glances at the current approaches to control ROS for improved skeletal tissue healing, including medicinal approaches, cellular engineering, and enhanced tissue scaffolds. This review aims to provide a nuanced view of the effects of ROS on bone fracture healing which will inspire novel techniques to optimize the redox environment for skeletal tissue regeneration.